1978
DOI: 10.1021/j100490a011
|View full text |Cite
|
Sign up to set email alerts
|

Orientational order and excess entropies of alkane mixtures

Abstract: According to eq 7, the observed activation energy of ketyl formation represents £5 -£4, where E4 and £5 are the activation energies of reactions 4 and 5, respectively. Since £4 is thought to be small, the observed value of 12 kcal mol"1 almost corresponds to the activation energy for the escape of radicals from the solvent cage, which would be controlled by diffusion. Assuming the diffusion rate of radicals from the cage is the same as the self-diffusion rate of the solvent, the observed value of 12 kcal mol"1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

1979
1979
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 4 publications
2
13
0
2
Order By: Relevance
“…Similar discrepancies were found for the smaller solvent in Figure 10 and one other solvent that Sharp et al studied (98). 3 Therefore, we are not yet persuaded that free volume models account for the Shinoda-Hildebrand data. 4 Either free volume effects in solution are small, or free volume does not distribute globally, as such models assume (90a).…”
Section: Shinoda-hildebrand Iodine Experimentssupporting
confidence: 66%
“…Similar discrepancies were found for the smaller solvent in Figure 10 and one other solvent that Sharp et al studied (98). 3 Therefore, we are not yet persuaded that free volume models account for the Shinoda-Hildebrand data. 4 Either free volume effects in solution are small, or free volume does not distribute globally, as such models assume (90a).…”
Section: Shinoda-hildebrand Iodine Experimentssupporting
confidence: 66%
“…7. These shapes are the outcome of the interplay of various factors, such as the breakage Table 6 Excess enthalpies for the binary of hydrogen bonds, the occurrence of -hydroxyl-aromatic ring interactions and even the endothermic breakage of liquid-crystal-like structures (orientation order of alkane mixtures [16]). …”
Section: Resultsmentioning
confidence: 99%
“…The higher H E values are exhibited by the binary with n-octane. This is attributed to the bigger size of n-octane, resulting in more extensive breaking of the above interactions between the molecules of 2-ethoxyethanol and also to the endothermic breakage of its liquid-crystal-like orientation order of n-alkane mixtures [16].…”
Section: Discussionmentioning
confidence: 99%
“…n-Alkanes are highly ordered in the solid state, existing in many crystalline phases which depend on the chain 0021 length [6]. In the liquid state they still retain much of their order, as was proved in the literature [7]. Using a light scattering technique it was showed that globular or spherical solvents destroy the conformational order in liquid long-chain hydrocarbons, giving high positive values for the enthalpy and entropy of mixing [8].…”
Section: Introductionmentioning
confidence: 78%